Nurses' Knowledge regarding Transfer of Critically Ill Patient at Kathmandu Nepal (Okhaldhunga Journal, 2026)
A critically ill patient is a person who has a very serious health problem that could be life threatening. Transferring critically ill patients from the intensive care unit to other departments for procedures or tests must be well organized and efficient. Nurses are the responsible individuals in the transportation of patients, a person in the transport of a patients with proper knowledge, will help to reduce the risk during transfer. The objective of this study is to assess knowledge regarding the transfer of critically ill patients among nurses working in Kathmandu Model Hospital, Kathmandu Nepal. A descriptive cross sectional study design was used. The non-probability purposive sampling technique was used to recruit 98 nurses. A semi structured self-administered questionnaire was developed which consisted of two parts. A questionnaire was distributed to the participants in their feasible time and 25 to 30-minutes time was given to fill up the questionnaire. The filled questionnaires were collected immediately after the completion. The data were analyzed through descriptive statistics (frequency, percentage) and inferential statistics (Chi-square). This study found that 22.4% of respondents had a higher knowledge however 46.9 % had a moderate level of knowledge and 30.6% of the respondents had a low level of knowledge. There was no statistically significant association between knowledge level and demographic variables. The study concludes that only one-third of the participants had good knowledge regarding the transfer of critically ill patients. Ongoing in-service education, regular training, and practical skill development programs were recommended to enhance nurses’ competency in the safe transfer of critically ill patients.